Baicalin Liposome Alleviates Lipopolysaccharide-Induced Acute Lung Injury in Mice via Inhibiting TLR4/JNK/ERK/NF-κB Pathway - Yu Long; Yan Xiang; Songyu Liu; Yulu Zhang; Jinyan Wan; Qiyue Yang; Mingquan Cui; Zhimin Ci; Nan Li; Wei Peng (Mediators of Inflammation)
Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are challenging diseases with the high mortality in a clinical setting. Baicalin (BA) is the main effective constituent isolated from the Chinese medical herb Scutellaria baicalensis Georgi, and studies have proved that it has a protective effect on ALI induced by lipopolysaccharide (LPS) due to the anti-inflammatory efficacy. However, BA has low solubility which may limit its clinical application. Hence, we prepared a novel drug delivery system—Baicalin liposome (BA-LP) in previous research—which can improve some physical properties of BA. Therefore, we aimed to explore the effect of BA-LP on ALI mice induced by LPS. In pharmacokinetics study, the values of t1/2 and AUC0-t in the BA-LP group were significantly higher than that of the BA group in normal mice, indicating that BA-LP could prolong the duration time in vivo of BA. The BA-LP group also showed a higher concentration in lung tissues than the BA group. Pharmacodynamics studies showed that BA-LP had a better effect than the BA group at the same dosage on reducing the W/D ratio, alleviating the lung injury score, and decreasing the proinflammatory factors (TNF-α, IL-1β) and total proteins in bronchoalveolar lavage fluids (BALF). In addition, the therapeutic effects of BA-LP showed a dose-dependent manner. Western blot analysis indicated that the anti-inflammatory action of BA could be attributed to the inhibition of the TLR4-NFκBp65 and JNK-ERK signaling pathways. These results suggest that BA-LP could be a valuable therapeutic candidate in the treatment of ALI.